1995
DOI: 10.1016/s0092-8674(05)80004-2
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of an AII-RNAhammerhead ribozyme: A proposed mechanism for RNA catalytic cleavage

Abstract: We have solved the crystal structure of an all-RNA hammerhead ribozyme having a single 2'-O-methyl cytosine incorporated at the active site to prevent cleavage. The conditions used differ from those in another recent solution in four significant ways: first, it is an all-RNA ribozyme rather than a DNA-RNA hybrid; second, the connectivity of the ribozyme backbone strands is different; third, the crystals were grown in the presence of a much lower concentration of salt; and fourth, the crystal packing scheme is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
609
0
5

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(659 citation statements)
references
References 32 publications
45
609
0
5
Order By: Relevance
“…Almost all crystallographic studies to date have indicated that a metal ion (P9 metal ion), such as Mn 2 , Cd 2 or Mg 2 , is bound by the pro-Rp oxygen (P9 oxygen) of the phosphate moiety of A 9 and N7 of G 10.1 (Pley et al 1994;Scott et al 1995). In some cases, the metal ion can be directly coordinated to N7 of G 10.1 (Scott et al 1996;Murray et al 1998a, b) and the sequence motif in such cases is known to be a metal-binding motif (Baeyens et al 1996;Peracchi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all crystallographic studies to date have indicated that a metal ion (P9 metal ion), such as Mn 2 , Cd 2 or Mg 2 , is bound by the pro-Rp oxygen (P9 oxygen) of the phosphate moiety of A 9 and N7 of G 10.1 (Pley et al 1994;Scott et al 1995). In some cases, the metal ion can be directly coordinated to N7 of G 10.1 (Scott et al 1996;Murray et al 1998a, b) and the sequence motif in such cases is known to be a metal-binding motif (Baeyens et al 1996;Peracchi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they can bind between the N7 of G 10.1 and the pro-Rp oxygen (P9 oxygen) of the phosphate moiety of A 9 , modulating the activity of the ribozyme. Almost all crystallographic and biochemical studies to date have suggested that N7 of G 10.1 and the pro-Rp oxygen of the phosphate moiety of A 9 are ligated with a metal ion (the conserved P9 metal) and that this bound metal ion is catalytically important (Buzayan et al 1990;Ruffner & Uhlenbeck 1990;Ruffner et al 1990;Tuschl & Eckstein 1993;Pley et al 1994;Scott et al 1995Scott et al , 1996Peracchi et al 1996Peracchi et al , 1997Murray et al 1998a, b;Wang et al 1999;Yoshinari & Taira 2000). In some cases, another metal-binding site has been found close to G 5 and replacement here of Mg 2 by Tb 3 inhibited the cleavage reaction (Feig et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past decade has seen a vast increase in structural data on complex tertiary structures of RNA, beginning with the hammerhead ribozyme [1][2] and culminating in the atomic resolution structures of both the small (30S) [3][4] and large (50S) [5] ribosomal subunits. The recently published 5.5Å structure of the complete (70S) ribosome [6] indicates that this trend is likely to continue.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of sequences near the cleavage site of several self-cleaving plant RNAs has led to the identification of a consensus secondary structure termed the 'hammerhead' [6]. Recently, the three-dimensional structure of the hammerhead ha~ been described [7,8]. The hammerhead consists of three heiices of variable length and a sequence of 11 unpaired nucleotides surrounding the cleavage site.…”
Section: Introductionmentioning
confidence: 99%